First manic/hypomanic episode in obsessive-compulsive disorder patients treated with antidepressants: A systematic review. (May 2021) - Bertolín, Sara; Alonso, Pino; Segalàs, Cinto; Real, Eva; Alemany-Navarro, María; Soria, Virginia; Jiménez-Murcia, Susana; Crespo, José Manuel; Menchón, José M.
Abstract: High doses of antidepressants, particularly clomipramine and selective serotonin reuptake inhibitors (SSRIs), are the well-established treatment for obsessive-compulsive disorder (OCD), but manic/hypomanic episodes are potential adverse events associated with this treatment. A systematic literature review was performed on manic/hypomanic episodes in non-bipolar OCD patients. Clinical, sociodemographic and antidepressant characteristics during the manic/hypomanic switch were extracted using descriptive statistics. Data were obtained from 20 case reports and case series. Switching episodes mostly appeared in the first 12 weeks after antidepressant initiation and took place more frequently during SSRI use (mostly fluoxetine) in 64.3% of cases. Clomipramine and SSRI use differed non-significantly between the switching episodes that appeared during the first 12 weeks of antidepressant treatment and the episodes that appeared beyond 12 weeks. Switching episodes emerging before 12 weeks were associated with a lower defined daily dose of antidepressants than episodes emerging after 12 weeks. These findings suggest that there are two independent characteristics involved in manic/hypomanic switch in OCD: a) they appeared most frequently with SSRI use (fluoxetine) regardless of the time of it use, and b) episodes appeared in the first 12 weeks after SSRI or clomipramine initiation had a lower dose of antidepressant than episodes appeared after 12 weeks.